An overview of prior patents for the sequential progress in the synthetic approaches of Rasagiline, its salts, crystallographic forms and impurities - Sukumar Saralaya, Sanjay (Indian Journal of Pharmacy & Drug Studies, 2024)
This review work was intended to provide the essential details disclosed in prior patents on the synthesis of Rasagiline, its salts (as crystalline or amorphous forms) and a few impurities. Quite a high number of patents were published in various patent trademark offices around the world regarding the synthesis of Rasagiline. Among them, the patents which fall under the similar family are excluded to prevent the possible duplication of the information. The remaining distinct patents were carefully reviewed and the particulars are grouped in chronological order. Moreover, this initiative can provide an essential backyard for the global researchers and the organizations to get the details on the methodological flourish of Rasagiline. More importantly, the work forms a firm basis for to invent/innovate a few more new strategies to commercialize Rasagiline in its pharmaceutically suitable and stable forms. Additionally, researchers can avail the information about the organizations which are behind the continuous process improvement on various aspects of Rasagiline.